2019 7th Workshop on Modeling and Simulation of Cyber-Physical Energy Systems (MSCPES) 2019
DOI: 10.1109/mscpes.2019.8738802
|View full text |Cite
|
Sign up to set email alerts
|

Cyber-physical simulation platform for security assessment of transactive energy systems

Abstract: Transactive energy systems (TES) are emerging as a transformative solution for the problems that distribution system operators face due to an increase in the use of distributed energy resources and rapid growth in scalability of managing active distribution system (ADS). On the one hand, these changes pose a decentralized power system control problem, requiring strategic control to maintain reliability and resiliency for the community and for the utility. On the other hand, they require robust financial market… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 16 publications
0
16
0
Order By: Relevance
“…They showed that maximizing local energy transactions also maximizes the overall utility. Essentially, most community-based methods such as in [56], [61], [62] typically focus on developing effective ways to optimize the MCP to be used between participants to optimize the balance between the demand and supply of energy.…”
Section: E Transactive Mechanisms For the Different Architecturesmentioning
confidence: 99%
“…They showed that maximizing local energy transactions also maximizes the overall utility. Essentially, most community-based methods such as in [56], [61], [62] typically focus on developing effective ways to optimize the MCP to be used between participants to optimize the balance between the demand and supply of energy.…”
Section: E Transactive Mechanisms For the Different Architecturesmentioning
confidence: 99%
“…[#11]: The paper describes the Transactive Energy Security Simulation Testbed (TESST) by Zhang et al, 72 a testbed for simulating cyber attacks in energy pricing. The authors have used PYPOWER, GridLAB‐D, ns‐3, and EnergyPlus for modeling transmission, distribution, telecommunication, and buildings, respectively.…”
Section: Co‐simulation Features For Modeling Cyber‐physical Securitymentioning
confidence: 99%
“…The collected security data can be utilized to create accurate virtual models representing different smart city applications/environments. These models can then be used to simulate different situations and security issues to identify problem areas [77]. For example, simulating a DDoS attack on the smart building management systems in a smart city and evaluating the impact on the buildings controls and residents.…”
Section: Security Modeling Simulation and Visualization Capabilimentioning
confidence: 99%